Effect of blood on physical-chemical properties and discoloration of experimental silicate cement and MTA HP - Canali, Lyz Cristina Furquim (2019)
The aim of this study was to analyze a Portland cement-based experimental cement with radiopacifiers (calcium tungstate, zirconium oxide and barium sulfate) and the HPMTA radiopacity, setting time, thickness, flow, pH, volumetric change, calcium ion release, release of nitric oxide NO, tooth discoloration and compression strength, the effect when in contact with blood. In 6 groups: I (CS) - Portland Cement; II (CSCT1) - 60% Portland cement + 30% Calcium tungstate and 10% barium sulphate; III (CSCT2) - 60% Portland cement + 20% Calcium tungstate and 20% barium sulphate; IV (CSCT3) - 60% Portland cement + 30% Calcium tungstate and 10% Zirconium oxide; V (CSCT4) - 60% Portland cement + 20% Calcium tungstate and 20% Zirconium oxide; VI HPMTA. 30% glycerin added to the distilled water. The radiopacity, ISO 6876/2001 (ISO, 2001), n.10 with 5 blood. The settling time standard ASTM C266/08, n.6 with 3 to blood. The flow and thickness standard ISO 6876/2001 (ISO, 2001). For pH, solubility and release of calcium ions, acrylic teeth with retrograde cavities, n.10 with 5 to blood and immersed in distilled water. The pH and release of calcium ions in the periods of 3h, 7h, 24h, 72h, 168h and 360h. Volumetric change in Micro CT initial time and 7 days. The production of NO by the Griess reaction. The spectrophotometry by INTERNATIONAL COMMISION ON ILLUMINATION (1978), 10 bovine teeth, periods of 7, 15, 30 and 60 days. Compression strength ISO 1997 (2007), n.12 with 6 to blood. It resulted in radiopacity within the recommended or above, a longer setting time and without interference with blood, higher flow and lower thickness compared to HPMTA, similar volumetric change compared to HPMTA. The pH and calcium release were slightly higher for the HPMTA cement. Acceptable cytotoxicity since the levels of these changes are so discrete. Spectrophotometric the CSCT1 and HPMTA presented slight significant change and the compression strength good resistance without interference to blood. The experimental cements had adequate properties to be used.